(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Could art Budaiya to find a prominent place in the media rhetoric belonging to the artistic statement and meanings, This art was soon later to become an art in itself exists independently, However, the difficulty of the configuration process and the evolution of the hand, Great development of the long-arts Budaiya after entering the field of rhetoric on the other hand, This led to the rhetorical differences on the labels of many of these arts, As well as on the enrollment of some magnificent arts and other arts, as annexation Epanalepsis to Echoing. Or make the opposite switch kind of the Epanalepsis. And other confusion in terminology and the complexity of the labels. The Epanalepsis and one of those arts that revolved around the views rhetorical. It is the art of repetition texture Bdiei, However, this repetition does not stop at the level of vocabulary words, Nor the characters and movements, But beyond that to form the most present in the line of poetry rhythmic and semantic side, This research will talk about those semantic and rhythmic aspects of this art, And through the application addressed to the poems Andalusian(Ahmad ibn Abd Rabbo,246-328), That was the rhythms and tonalities export Remember well attended by it.